Development of Gluten-Free Noodles Based on Cassava–Bambara Groundnut Composite Flour - Akwetey, Ebenezer Bassey (University of Cape Coast, 2024)
Noodles are now a common food in the World, eaten by many from different cultural backgrounds and races. However, noodles made from wheat are often seen as less healthy. As people become more health-conscious, researchers are experimenting with different ingredients to make noodles that are healthier, gluten-free, and meet changing food preferences. The study was centered on the development of gluten-free noodles from Casava-Bambara groundnut composite flour and the determination of the functional, textural, colour, sensory and nutritional composition of the resulting noodles. A simplex centroid mixture design in Minitab software was used for the formulations with the two mixture variables: Cassava flour [X1 (% w/w)] and Bambara groundnut flour [X2 (% w/w)] equaling 100 %. The ash, protein and fibre contents significantly increased (from 0.84 % to 1.52 %, 4.16 % to 7.27 % and 3.01 % to 4.48 % respectively) whereas the moisture and carbohydrate contents decreased (from 8.35 % to 7.35 and 87.23 % to 82.84 % respectively) as the percentage of Bambara Groundnut Flour increased. In addition, zinc, calcium, magnesium, iron, and potassium for Bambara Groundnut Flour incorporated noodles increased. Cooking losses were also minimal for formulations containing Bambara groundnut flour compared to the noodles prepared from 100 % Cassava Flour. Noodles with 30 % Bambara Groundnut Flour was the most preferred after the sensory evaluation. The results are relevant for utilizing Bambara groundnut as an ingredient in gluten-free noodle production as its addition improved the functional properties, nutritional composition and sensory attributes.
xii,85p:, ill.
Keywords: Noodles Bambara groundnut Cassava flour Gluten-free noodles Nutritional composition